2018
DOI: 10.1111/jvh.12943
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of unrestricted direct‐acting antiviral treatment for hepatitis C in Australia: The South Australian statewide experience

Abstract: In March 2016, the Australian government offered unrestricted access to direct-acting antiviral (DAA) therapy for chronic hepatitis C virus (HCV) to the entire population. This included prescription by any medical practitioner in consultation with specialists until sufficient experience was attained. We sought to determine the outcomes and experience over the first twelve months for the entire state of South Australia. We performed a prospective, observational study following outcomes of all treatments associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
2
25
1
1
Order By: Relevance
“…This is consistent with the notion of ‘warehousing’ where patients had already been assessed for treatment and were waiting for DAA therapy to become available 17. We were able to show an increase in prescribing in the most recent months, the majority of which were in primary care.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the notion of ‘warehousing’ where patients had already been assessed for treatment and were waiting for DAA therapy to become available 17. We were able to show an increase in prescribing in the most recent months, the majority of which were in primary care.…”
Section: Discussionsupporting
confidence: 87%
“…Rates of loss to follow-up and therefore incomplete SVR data have previously been shown to be higher in this group 16. This is likely due to the higher prevalence of active injecting drug use, younger age and lower prevalence of advanced liver disease in primary care cohorts 17. Strategies such as early follow-up between end of treatment and SVR in addition to incentives are being explored 18…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapid advances in DAA treatments and their high effectiveness, LTF remains a significant barrier in the HCV treatment cascade and could impact the overall effectiveness of treatment. In this study, the overall LTF rate of 10% was lower than the rates reported in a real‐world study conducted in South Australia among GT1‐ and GT4‐infected individuals (14.2%) and in Egypt among GT4‐infected patients (29%) . However, our findings indicate that: 1) LTF, including death, exceeds viral failure with HCV DAA therapy and requires considerable attention in the HCV elimination pathway; and 2) LTF rates vary significantly by genotype and treatment regimen.…”
Section: Discussioncontrasting
confidence: 77%
“…Third, as the assessment of factors contributing to SVR and LTF rates (eg IDU, cirrhosis) were based on diagnostic codes, misclassification of these variables is possible (Table ). As ‘homelessness’ status was not available in our data, the potential association between this variable and LTF could not be measured . For LTF assessment, due to the low power, multivariable models could only be conducted for the overall and LDV/SOF ± RBV treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation